Meningkatkan Hasil Belajar Struktur dan Fungsi Bagian Tumbuhan Menggunakan Model Pembelajaran Think Pair Share (TPS) Bagi Siswa Kelas IV SD Negeri Indomut, Kabupaten Halmahera Selatan - Munir Latukau; Fajrini Samad; M. Iksan B. Aly; Usman Amiruddin; Apridayani Marasabessy (Jurnal Inovasi Pendidikan dan Pembelajaran Sekolah Dasar, 2021)
The purpose of this study was to determine the increase in learning outcomes of the Main Science Study of the Structure and Function of Plant Parts with the Application of the Think Pair Share (TPS) Cooperative Learning Model for Class IV Students at SD Negeri Indomut, South Halmahera Regency. The research method is Classroom Action Research with stages: planning, action implementation, observation, evaluation, and reflection. Learning outcomes showed an increase: (1) Cycle I: Before being given treatment, as many as 11 students (65%) scored below 65, and only 6 students (35%) scored above 65 increased to 9 students (52.94%) got a score below 65, and 8 students (47.06%) got a score above 65; (2) Cycle II: there was a more significant increase. The learning outcomes of 17 students, as many as 9 students (52.94%) got scores below 65, and 8 students (47.06%) got scores above 65. Learning outcomes increased after the second cycle was carried out which obtained an average grade value above 65. overall to 82.35%.